External Equitable Domination in Graphs - et al., D. Lakshmanaraj (International Journal of Advanced Science and Technology, 2019)
This paper aims at the study of a new concept called external equitability. Properties like independence, excellence, domination etc are coupled with external equitability and a detailed study is made.